Improving the Fiscal Sustainability of Teaching Clinics at Dental Schools. Issue 12 (1st December 2015) - Reinhardt, John W.
Abstract : Educational patient care clinics are becoming an increasingly important source of revenue for dental schools. Revenue from clinics can help offset the rising cost of dental education. In addition, those clinics represent a source of income over which the schools have reasonably direct control. Recently, a group of nine U.S. dental schools conducted a detailed financial survey of their clinics and shared the confidential results with each other. The purpose of their analysis was to develop benchmarks for key factors related to clinical financial productivity and expenses and to define best practices to guide improvements at each school. The survey found significant variations among the nine schools in revenue produced by predoctoral students and by postdoctoral residents. There were similar variations for levels of clinical staffing. By sharing the results of the survey with each other, the individual schools gained a strong understanding of the business strengths or weakness of their own clinical programs. That information gave each school's leaders the opportunity to investigate how they might improve their clinical fiscal sustainability.